The Comprehensive Systematic Review of Diagnostic Accuracy of Rapid Point of Care Tests for Syphillis - Hana Shabrina Purnama; Gema Putra Bangsa (International Medical Journal Corp. Ltd, 2026)
Introduction: Syphilis remains a significant global public health challenge, with congenital syphilis continuing as a leading cause of preventable stillbirth and neonatal death. Rapid point-of-care tests (POCTs) offer potential to expand screening access in resource-limited settings; however, comprehensive evidence synthesis regarding their diagnostic accuracy across diverse populations and test types is required to inform global policy. Methods: This systematic review synthesised evidence from 159 diagnostic accuracy studies identified through comprehensive database searches. Studies evaluating treponemal-only, nontreponemal-only, or dual treponemal/nontreponemal rapid tests against accepted reference standards (TPPA, TPHA, FTA-Abs, RPR, VDRL) were included. Data extraction encompassed test characteristics, study populations, reference standards, diagnostic accuracy metrics, performance modifiers, and methodological quality. Synthesis was structured by test category, specimen type, syphilis stage, HIV status, and testing conditions. Results: Treponemal-only tests demonstrated consistently high specificity (94.1–100%) but variable sensitivity (59.6–100%), with Abbott Determine TP (26 studies) and SD Bioline Syphilis 3.0 (18 studies) most extensively evaluated. Dual treponemal/nontreponemal tests (Chembio DPP Syphilis Screen & Confirm, SD Bioline HIV/Syphilis Duo) showed excellent treponemal component performance (sensitivity 66.0–96.7%; specificity 97.2–99.3%), but nontreponemal component sensitivity was substantially lower (42.9–94.2%), particularly at low RPR titres. Test sensitivity was significantly enhanced in high-titre (≥1:8) active syphilis (94.6–100%) and reduced in primary syphilis (77.3–100%) and when using fingerprick whole blood versus serum/plasma. Field-based evaluations generally yielded lower accuracy estimates than laboratory studies. Performance in HIV co-infected populations varied, with some studies demonstrating maintained or enhanced sensitivity but reduced specificity. Discussion: This review identifies critical research gaps including limited standardisation of reference standards and case definitions, insufficient reporting of blinding procedures, heterogeneous definitions of active syphilis, underrepresentation of primary syphilis cases, and few head-to-head comparisons of multiple test brands. The novelty of this synthesis lies in its comprehensive stratification of performance by test type, specimen, disease stage, and population subgroup, enabling nuanced, context-specific test selection guidance. Conclusion: Rapid syphilis POCTs demonstrate sufficient accuracy for screening in resource-limited settings, particularly for high-titre active infections. Treponemal-only tests effectively rule out infection but cannot distinguish active from past disease. Dual tests offer improved clinical utility for identifying active syphilis requiring immediate treatment, although reduced nontreponemal component sensitivity at low titres may result in missed active infections. Test selection should be guided by local epidemiology, prevalence, available resources, and specific programmatic objectives. Rigorous training, quality assurance, and confirmatory testing algorithms remain essential implementation prerequisites.